The voice : a novel - Myers, Bill, 1953- (New York : Faith Words, 2008)
Former Special Forces Agent Charlie Madison comes out of retirement to help his niece find her parents, who disappeared after creating a computer program that has recorded the actual voice of God.
Adult
Adult
Library Journal
Booklist
Keywords: Missing persons -- Fiction; Missing persons -- Fiction; Christian fiction; Adventure fiction; Christian fiction; Adventure fiction